2018
DOI: 10.31729/jnma.3791
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophic Epidermolysis Bullosa

Abstract: Epidermolysis bullosa is a rare inherited blistering disease with an incidence of 8-10 per million live births. Dystrophic epidermolysis bullosa is a type of epidermolysis bullosa caused by mutation in type VII collagen, COL7A1. There are 14 subtypes of dystrophic epidermolysis bullosa and 400 mutations of COL7A1. Electron microscopy is the gold standard diagnostic test but expensive. Immunofluorescence study is a suitable diagnostic alternative. Trauma prevention along with supportive care is the mains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, follow-up data demonstrated that only a subset of patients had their hands fixed with braces. The main reason is that as the disease progresses, some clinical symptoms of DEB patients, including blisters on the skin of the whole body, mucosal ulcers, etc., gradually worsen with time ( 16 ), making everyday care more challenging. DEB patients who eventually develop systemic diseases die of squamous cell carcinoma ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, follow-up data demonstrated that only a subset of patients had their hands fixed with braces. The main reason is that as the disease progresses, some clinical symptoms of DEB patients, including blisters on the skin of the whole body, mucosal ulcers, etc., gradually worsen with time ( 16 ), making everyday care more challenging. DEB patients who eventually develop systemic diseases die of squamous cell carcinoma ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, follow-up data demonstrated that only a subset of patients had their hands xed with braces. The main reason is that as the disease progresses, some clinical symptoms of DEB patients, including blisters on the skin of the whole body, mucosal ulcers, etc., gradually worsen with time [15], making everyday care more challenging. DEB patients who eventually develop systemic diseases die of squamous cell carcinoma [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The disease has an incidence of 0.08-0.5 per million live births, occurs among all ethnicities, and is inherited either from one of the parents or both due to deficiency in several genes. [1][2][3] Recessive dystrophic EB (RDEB) is attributed to the bi-allelic loss-offunction mutations in COL7A1 (3p21.31), a gene expressed by skin keratinocytes and fibroblasts which encodes type VII collagen (C7). 4 C7 is the main component of anchoring fibrils (AFs) which ensures the adherence of the epidermis to the dermis within the basement membrane.…”
Section: Introductionmentioning
confidence: 99%